The One Is the Many: Buddhist Relational Holism in Uno e altri amori by Carlo Coccioli - Dellacasa, Claudia (Quaderni d'Italianistica)

(untitled) (Iter Press, 2024)
The literary production of Carlo Coccioli in the 1980s is characterized by a growing interest in Hinduism and Buddhism, supported by and in turn reinforcing his strong sense of compassion and proximity towards more-than-human forms of life. In particular, in the collection of short stories Uno e altri amori (1984), animals represent a comforting spiritual presence that remains persistent even as the religious and spiritual framing evolves. This essay discusses Coccioli’s horizontal relationship with animals in the light of a relational holism that derives from the author’s interest in Buddhism, in which the absolute and the relative, as well as the one and the many, are conceived in relations of mutual determination. The analysis focuses specifically on three short stories from Uno e altri amori—“Se ci fosse, si saprebbe,” “L’asciugamano di spugna,” and “Salmo XXIII (o theological spiders)”—in which questions of faith are overtly foregrounded, at the same time situating the collection as a whole in the context of Coccioli’s key texts of the 1980s and 1990s: La casa di Tacubaya (1982), Piccolo Karma (1987), and Budda e il suo glorioso mondo (1990).